Twin pregnancy-maternal and fetal complications its association with mode of delivery: a study in a tertiary center - Pyrbot, Jupirika E.; Agarwal, Manika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Twin pregnancies are associated with many complications. Hence the mode of delivery and its effect on the maternal and foetal outcome is important. Methods: A retrospective study of twin pregnancies carried out from April 2015 to March 2017 in a tertiary hospital in north east, India. The maternal, foetal outcome and the mode of delivery data collected and analysed. Results: A total of 50 twin pregnancies studied. The prevalence of twin was 20/1000 deliveries. Most common age group was 20-29 years with a mean age of 28±5.7 years. A total of 24 (48%) had vaginal delivery and 26 (52%) had LSCS, 2 (4%) had the first twin as vaginal delivery and second twin LSCS. A statistical significance was seen in the mode of delivery of twin pregnancies conceived after ovulation induction, (p<0.05). The most common indication for LSCS was foetal malpresentation (14.58%) followed by foetal distress (12.5%) and elective LSCS (10.42%) on patient’s request. The most common complication was anaemia (28.08%) and PIH (27.08%). In the neonate prematurity was the most common morbidity. There was no association between the mode of delivery and the foetal outcome in the form of Apgar at 5 minutes, NICU admission and perinatal mortality. Conclusions: There is a rise of caesarean delivery in twin pregnancies, maternal request becoming one of the causes. Regular antenatal check-ups of pregnant women with counselling regarding the mode of delivery should be carried out.